A short review on susceptibility to falling for fake political news. (December 2020) - Sindermann, Cornelia; Cooper, Andrew; Montag, Christian
Highlights: Accuracy of true and fake news consistent with own political attitudes is overrated. Analytical thinking and susceptibility to falling for fake news are negatively related. Deliberation reduces susceptibility to falling for fake news. News consumption habits should be investigated in future studies. External validity of fake news tests needs to be considered. Abstract : This review discusses recent findings on susceptibility to falling for fake news in political contexts. In relation to political attitudes and analytical thinking, we find that individuals tend to overrate the accuracy of true and fake political news that are consistent with their own political attitudes. This tendency, however, does not seem to be explained by motivated reasoning. This is supported by findings showing that analytical thinking and deliberation are negatively related to susceptibility to falling for fake news, regardless of whether they are consistent or inconsistent with one's political attitudes. We suggest that future works should aim at i) examining how, for example, news consumption habits relate to susceptibility to falling for fake news and ii) implementing other, more externally valid fake news tests.